2022
DOI: 10.1002/pmh.1556
|View full text |Cite
|
Sign up to set email alerts
|

The joint hierarchical structure of psychopathology and dysfunctional personality domain indicators among community‐dwelling adults

Abstract: To examine the hierarchical structure of psychopathology and dysfunctional personality domains, 2416 Italian community‐dwelling adult volunteers were administered a set of psychometrically sound psychopathology measures and the Personality Inventory for DSM‐5 Brief Form+ (PID‐5‐BF+). Parallel analysis, minimum average partial, and very simple structure results suggested that 1–6 principal components (PCs) should be retained. Goldberg's bass‐ackwards model of the joint psychopathology measure and PID‐5‐BF+ ipsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 88 publications
8
5
0
Order By: Relevance
“…The Internalizing/ Detachment and Externalizing/Thought Disorder dimensions met Goldberg's criteria (Loehlin and Goldberg 2014) for a likely hierarchical structure. Our findings are similar to those of Somma et al (2022), who found a broad internalizing and "non-internalizing" component at level two of their "bass-ackwards" hierarchy. The Somma et al (2022) non-internalizing component "included indicators from both the Externalizing and Thought Disorder spectra" (Somma et al 2022, p. 18), a finding similar to the Externalizing/ Thought Disorder component obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The Internalizing/ Detachment and Externalizing/Thought Disorder dimensions met Goldberg's criteria (Loehlin and Goldberg 2014) for a likely hierarchical structure. Our findings are similar to those of Somma et al (2022), who found a broad internalizing and "non-internalizing" component at level two of their "bass-ackwards" hierarchy. The Somma et al (2022) non-internalizing component "included indicators from both the Externalizing and Thought Disorder spectra" (Somma et al 2022, p. 18), a finding similar to the Externalizing/ Thought Disorder component obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are similar to those of Somma et al (2022), who found a broad internalizing and "non-internalizing" component at level two of their "bass-ackwards" hierarchy. The Somma et al (2022) non-internalizing component "included indicators from both the Externalizing and Thought Disorder spectra" (Somma et al 2022, p. 18), a finding similar to the Externalizing/ Thought Disorder component obtained in the present study. Overall, these findings suggest that hierarchical transdiagnostic scales compatible with contemporary models of psychopathology can be derived from PAI and SPECTRA data.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations